Long-term outcomes of combined endoscopic resection and chemoradiotherapy for esophageal squamous cell carcinoma with submucosal invasion. Issue 8 (August 2018) - Yoshimizu, Shoichi; Yoshio, Toshiyuki; Ishiyama, Akiyoshi; Tsuchida, Tomohiro; Horiuchi, Yusuke; Omae, Masami; Hirasawa, Toshiaki; Asari, Takao; Chin, Keisho; Fujisaki, Junko
Abstract: Background: For esophageal squamous cell carcinoma (ESCC) with submucosal (SM) invasion, surgery is the standard treatment. Definitive chemoradiotherapy (D-CRT) is a less invasive alternative option, but sometimes results in locoregional failure. Aim: To examine whether endoscopic resection for primary lesion removal combined with chemoradiotherapy (ER-CRT) reduces locoregional failure rates in cases of ESCC with SM invasion. Methods: We retrospectively compared clinical outcomes between ER-CRT and D-CRT in patients diagnosed with ESCC with SM invasion between 2003 and 2014. Twenty-one patients underwent ER-CRT based on a pathological diagnosis, and 43 patients underwent D-CRT based on a clinical diagnosis. Results: Locoregional failure developed in 26% of patients in the D-CRT group, and in no patients in the ER-CRT group ( p  < 0.01). Thus, the 5-year relapse-free survival in the ER-CRT group was significantly more favorable than that in the D-CRT group (85.1% vs 59.2%; p  < 0.05), although there was no difference in overall survival (85.1% vs 79.1%) nor in cause-specific survival (90.5% vs 87.2%) between the groups. There were no instances of perforation or hemorrhage associated with ER. Conclusion: ER-CRT is a safe and effective treatment strategy and can be considered as a new minimally invasive treatment option for patients with ESCC with SM invasion.